What should public governance be: review on the book: Zotov V. V. [ed.] (2021), Public administration in a digital society: to a new social contract: monograph, University Book, Kursk, Russia (in Russian) - R. N. Korchagin (Цифровая социология)
A review of the monograph “Public administration in a digital society: to a new social contract” is presented. The book under review is devoted to the development of a scientifically based concept of the social contract of the digital society. According to the authors, the modern period of state development, the period of searching for better and more targeted forms of interaction between the authorities and the population significantly expands the possibilities of mass participation of the population in state governance using information and telecommunication technologies. The authors make the conclusion that humanity is in the widest range of options – from strengthening the tendencies of the state, whose supervisory functions may be too total in relation to the person, to digital consensus democracy, when citizens are able to reach agreements on a wide range of socially significant tasks. The book proposes the use of digital network platforms as communication platforms that ensure the establishment of a certain level of trust between citizens and the population. This is a research publication, that introduces the government and municipal employees, representatives of science, education and of public organisations and political parties, all interested in the range of modern problems of social development in the context of the digital transformation of most public spheres and the public administration transformation.